Social Determinants of Health in Patients Undergoing Open Reduction and Internal Fixation for Distal Radius Fractures - Gordon, Adam M.; Elali, Faisal R.; Choueka, Jack (Journal of Wrist Surgery, 2025)
Background Social determinants of health (SDOH) may influence hand surgery outcomes. The Area Deprivation Index (ADI) is a validated and weighted index comprised of 17 census-based markers of material deprivation and poverty.Questions/Purpose The purpose was to determine whether patients with high ADI (greater disadvantage) undergoing open reduction and internal fixation (ORIF) for distal radius fractures (DRF) were associated with differences in: (1) medical complications, (2) emergency department (ED) utilizations, (3) readmissions, and (4) costs.Materials and Methods Patients who underwent ORIF for DRFs were isolated from an insurance database from 2010 to 2020. ADI is reported on a scale of 0 to 100. Higher numbers indicate greater disadvantage. Patients associated with high ADI (95% + ) were compared with controls defined as lower ADI (0–94%). Patients with high ADI were 1:1 propensity-score matched to controls by age, gender, and Elixhauser Comorbidity Index (ECI). Multivariable logistic regression models computed odds ratios (OR) of ADI on medical complications, ED utilizations, and readmissions. t-tests were used to compare costs. P-values less than 0.05 were considered significant.Results Patients undergoing ORIF for DRF from high ADI incurred higher rates and odds of developing all medical complications (5.58 vs. 4.63%; OR: 1.23, p < 0.0001). It was found that 90 ED utilizations (0.80% vs. 0.97%; OR: 0.83, p = 0.087) and readmissions (2.71% vs. 2.52%; OR: 1.08, p = 0.243) were similar to controls. Day of surgery ($2,626 vs. $2,571) and 90-day expenditures ($5,019 vs. $4,783) were similar between groups (all p > 0.185).Conclusions Socioeconomically disadvantaged patients have increased rates and odds of 90-day medical complications following ORIF for DRFs.Level of Evidence III.
Keywords: area deprivation index; complications; distal radius fractures; healthcare disparities; socioeconomic